Ibn ‘Arabi dan Paham Wahdat al-Wujud - Zainun Kamaluddin Fakih (Refleksi: Jurnal Kajian Agama dan Filsafat, 1998)
Waḥdat al-wujūd means: the Unity of Being, meaning that there is only one existence, which is the existence of Allah. The plural forms observed in the world are illusions that dominate the limitations of the intellect. This concept was born in Spain (Andalusia) or the western Islamic region, and then spread to the eastern Islamic regions. Its notable figure is Muḥy al-Dīn Ibn ‘Arabī. From this concept of waḥdat al-wujūd arose the idea of the perfect human (insan kamil). This idea can be found in Fushush al-Ḥikām and Futuḥat al-Makkiyah.